Holocene glacier fluctuations at Eklutna Lake, Chugach Mountains, south-central Alaska - Hunter T. Allen; Darrell S. Kaufman; Nicholas P. McKay; Erik Schiefer; Laura J. Larocca; Britta J.L. Jensen; Matthew S.M. Bolton; Kathleen R. North; Nore Praet; Maarten Van Daele; Marc De Batist; Maurycy Żarczyński (Quaternary Science Reviews, 2026)

Chemical mohometry, thick and thin: Critical review and new steps forward - Matthew J. Kohn; Allen F. Glazner; Chris Yakymchuk; Armando Lopez; Gloria Roman (Earth-Science Reviews, 2026)

Machine learning-assisted gait analysis for lameness detection in heterogeneous dog populations - Lyndie Mitchell; Matthew Scott; Kirsten Häusler; Chiara Adami; Michael Sutcliffe; Matthew Allen (The Veterinary Journal, 2026)

Predator and prey density effects on early life-history performance of largemouth bass (Micropterus nigricans) in an indoor recirculating aquaculture system - Nelson S. Parajuli; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; D. Allen Davis; Timothy J. Bruce; Matthew K. Litvak; Ian A.E. Butts (Aquaculture, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Beyond size and shape: Physicochemical properties of microplastic test materials generated by cryomilling - Lucy Howarth-Forster; Robyn Barrett; Robert Clough; Lisbet Sørensen; Jack Allen; Chris Powell; Richard C. Thompson; Matthew Cole; Michael Wilde (Journal of Hazardous Materials, 2026)

Legacy mercury emissions and releases from colonial-era gold mining in Australia - Larissa Schneider; Fei Cao; Peter Davies; Kathryn Allen; Simon Apte; James River Taylor; Quan Hua; Josh King; Ruoyu Sun; Matthew Theodore Brookhouse; Susan Lawrence (Environmental Pollution, 2026)

Correction: Practical Application of Geophysical Methods for Characterisation of Waste Rock Dumps - Christopher C. Allen; Matthew J. Cracknell; Clare B. Miller; Owen P. Missen; Sebastien Meffre (Mine Water and the Environment, 2026)

Practical Application of Geophysical Methods for Characterisation of Waste Rock Dumps - Christopher C. Allen; Matthew J. Cracknell; Clare B. Miller; Owen P. Missen; Sebastien Meffre (Mine Water and the Environment, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Policy implications of net-zero emissions: A multi-model analysis of United States emissions and energy system impacts - John E.T. Bistline; Matthew Binsted; Geoffrey Blanford; Gale Boyd; Morgan Browning; Yongxia Cai; Jae Edmonds; Allen A. Fawcett; Jay Fuhrman; Ruying Gao; Chioke Harris; Christopher Hoehne; et al. (Energy and Climate Change, 2025)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Core-top constraints on the ecology and paleothermometry of planktic foraminifera in the Indian Ocean - Ryan H. Glaubke; Elisabeth L. Sikes; Natalie E. Umling; Katherine A. Allen; Matthew W. Schmidt (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Repeated low-dose copper algaecide treatments promote beneficial phytoplankton and zooplankton communities - Michael B. McDonald; Ashley V. Hennessey; Peyton P. Johnson; Matthew F. Gladfelter; Kate L. Merrill; Suzanne E. Tenison; Sathya S. Ganegoda; Tham C. Hoang; H. Allen Torbert; Benjamin H. Beck; Alan E. Wilson (Journal of Environmental Management, 2025)

Thermal treatment of hexafluoropropylene oxide dimer acid (HFPO-DA) using a pilot-scale research combustor - Nathan H. Weber; Gabrielle V. West; William R. Roberson; John C. Mackie; James M. Mattila; Preston Burnette; Matthew Allen; William Preston; William P. Linak; Jonathan D. Krug (Journal of Hazardous Materials, 2025)

Evaluation of co-foaming agents for enhanced removal of per-and polyfluoroalkyl substances (PFAS) by foam fractionation - Craig Klevan; Oren Van Allen; Shana Xia; Kelly Mukai; Andre Gomes; Seth Caines; Matthew J. Woodcock; Kurt D. Pennell (Journal of Hazardous Materials, 2025)

Reconciling scale using the Resist-Accept-Direct (RAD) Framework to improve management of woody encroachment in grasslands - Rheinhardt Scholtz; Daniel R. Uden; Brady W. Allred; Victoria M. Donovan; Jeremy D. Maestas; Scott L. Morford; Matthew O. Jones; David E. Naugle; Samantha M. Cady; Dillon T. Fogarty; Alexander L. Metcalf; Brian Chaffin; et al. (Journal of Environmental Management, 2025)

Accounting for sustainability and performance: Contrasting effects of PET-derived modifiers on asphalt durability - Saba Shariati; Mohammadjavad Kazemi; Husain Mithaiwala; Adarsh Bakkireddy; Robert B. Stirling; Robert D. Allen; Matthew D. Green; Elham H. Fini (Resources, Conservation and Recycling, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Evaluating the tolerance of harmful algal bloom communities to copper - Ashley V. Hennessey; Michael B. McDonald; Peyton P. Johnson; Matthew F. Gladfelter; Kate L. Merrill; Suzanne E. Tenison; Sathya S. Ganegoda; Tham C. Hoang; H. Allen Torbert; Benjamin H. Beck; Alan E. Wilson (Environmental Pollution, 2025)

Status of truffle science and cultivation in North America - Mark D. Coleman; Shannon Berch; Gregory Bonito; Brian Allen; Ellie Andrews; Elva T. Arechiga Carvajal; Stephen P. Cook; Cameron D’Amours; Roberto Garibay-Orijel; Gonzalo Guevara; Patrick Hatzenbuehler; Barbara Hawkins; et al. (Plant and Soil, 2025)
Background Truffles are subterranean fungal fruiting bodies that are highly prized for their culinary value. Cultivation of truffles was pioneered in Europe and has been successfully adapted in temperate regions throughout the globe. Truffle orchards have been established in North America since the 1980s, and while some are productive, there are still many challenges that must be overcome to develop a viable North American truffle industry. These challenges include extended delays between establishment and production, comparatively low yields, high spatial heterogeneity in yield distribution, and orchard contamination with lower-value truffle fungi. Aim Here we review known requirements for truffle production including necessary environmental conditions, reproductive biology, and effective agronomic practices. Content We consider the potential limitations of importing exotic host-fungal associations into North America where there is already a rich community of competing ectomycorrhizal fungi, host pests and pathogens. We also describe the status of the North American truffle industry with respect to market potential, including production costs, pricing, and biological and socioeconomic risk factors. A critical aspect of modern trufficulture involves monitoring with genetic tools that supply information on identity, abundance and distribution of fungal symbionts, abundance of competitive and contaminating fungi, and insight into the interactions between fungal mating types that are fundamental to the formation of truffle primordia. Implications Cultivation of the ectomycorrhizal truffle symbiosis requires application of pragmatic agronomic practices, adopting rigorous quality control standards, and an understanding of fungal biology, microbiology, and molecular biology. Consequently, significant interdisciplinary collaboration is crucial to further develop the North American truffle industry.

Validation and otolith-mass prediction of age and growth for cardinal snapper Pristipomoides macrophthalmus of the Caribbean Sea - Ivy E. Baremore; Allen H. Andrews; Simon J. B. Gulak; Rachel T. Graham; Matthew J. Witt; Virginia R. Shervette (Environmental Biology of Fishes, 2025)
Cardinal snapper Pristipomoides macrophthalmus is a commercially important, but commonly misidentified, deepwater species in artisanal and semi-industrial fisheries throughout the Caribbean Sea. As with many tropical deepwater fishes, little is known about the biology or ecology of the species. Bomb radiocarbon ( 14 C) dating was applied to cardinal snapper sagittal otoliths collected from the waters of Belize and Honduras during 2015–2019 to investigate the lifespan of the species from thin-sectioned otoliths with an evaluation of otolith mass as a proxy for age. Ages estimated from 28 thin-sectioned otoliths ranged from 7 to 68 years for fish that covered the range lengths and otolith masses available. Radiocarbon values were measured for each cardinal snapper otolith core, and two fish (one each from Belize and Honduras) had 14 C signatures consistent with pre-bomb values, effectively validating a lifespan of at least 60 years. A curvilinear relationship between otolith mass and estimated age was robust ( r 2 = 0.95) and is likely to produce age estimates with similar margins of error to traditional, more labor-intensive methods, such as counting increments from thin-sectioned otoliths. The otolith mass-to-age relationship is a well-supported method that provides a simple, low-cost approach that can be used by fishers, managers, and other stakeholders to assess the age composition of the cardinal snapper stock in the western Caribbean Sea for present and long-term monitoring.

First record of the seagrass Halophila stipulacea (Forsskal) Ascherson in the waters of the continental United States (Key Biscayne, Florida) - Justin E. Campbell; Aarin-Conrad Allen; Danielle C. Sattelberger; Matthew D. White; James W. Fourqurean (Aquatic Botany, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Influence of mixotrophy on cell cycle phase duration and correlation of karlotoxin synthesis with light and G1 phase in Karlodinium veneficum - Erik L.J.E. Broemsen; Jens Wira; Allen R. Place; Matthew W. Parrow (Harmful Algae, 2024)

A comparative analysis of OpenET for evaluating evapotranspiration in California almond orchards - Kyle Knipper; Martha Anderson; Nicolas Bambach; Forrest Melton; Zac Ellis; Yun Yang; John Volk; Andrew J. McElrone; William Kustas; Matthew Roby; Will Carrara; Sebastian Castro; et al. (Agricultural and Forest Meteorology, 2024)

An observation of potential altruism by a male northern elephant seal ( Mirounga angustirostris ) - Sarah G. Allen; Matthew J. Lau; Sarah A. Codde (Marine Mammal Science, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

An impact evaluation of conservation investments targeting long‐distance migratory species - C. Josh Donlan; Diana Eusse‐González; Gloria M. Luque; Matthew E. Reiter; Viviana Ruiz‐Gutierrez; Michael C. Allen; Richard Johnston‐González; Orin J. Robinson; Guillermo Fernández; Eduardo Palacios; Jorge Valenzuela (Conservation Biology, 2024)
We evaluated the impact of a philanthropic program investing in the conservation of sites along the Pacific Americas Flyway, which spans >16,000 km of coastline and is used by millions of shorebirds. Using a quasi‐experimental, mixed methods approach, we estimated what would have happened to shorebird populations at 17 wintering sites without the sustained and additional investment they received. We modeled shorebird populations across the entire flyway and at sites with and without investment. Combining shorebird abundance estimates with a land‐cover classification model, we used the synthetic control method to create counterfactuals for shorebird trends at the treatment sites. We found no evidence of an overall effect across three outcome variables. Species‐ and site‐level treatment effects were heterogeneous, with a few cases showing evidence of a positive effect, including a site with a high level of overall investment. Results suggest six shorebirds declined across the entire flyway, including at many Latin American sites. However, the percentage of flyway populations present at the sites remained stable, and the percentage at the treatment sites was higher (i.e., investment sites) than at control sites. Multiple mechanisms behind our results are possible, including that investments have yet to mitigate impacts and negative impacts at other sites are driving declines at the treatment sites. A limitation of our evaluation is the sole focus on shorebird abundance and the lack of data that prohibits the inclusion of other outcome variables. Monitoring infrastructure is now in place to design a more robust and a priori shorebird evaluation framework across the entire flyway. With this framework, it will prove easier to prioritize limited dollars to result in the most positive conservation outcomes.

Accelerating carbon neutrality in China: Sensitive intervention points for the energy and transport sectors in Beijing and Hong Kong - Sum Yue Chung; Matthew C. Ives; Myles R. Allen; Jay R.S. Doorga; Yuan Xu (Journal of Cleaner Production, 2024)

Forest soil classification for intensive pine plantation management: “Site Productivity Optimization for Trees” system - Rachel Cook; Thomas R. Fox; Howard Lee Allen; Chris W. Cohrs; Vicent Ribas-Costa; Andrew Trlica; Matthew Ricker; David R. Carter; Rafael Rubilar; Otávio Campoe; Timothy J. Albaugh; Pete Kleto; et al. (Forest Ecology and Management, 2024)

Impacts of flue gas desulfurization (FGD) gypsum on water quality and the algal community in catfish aquaculture ponds - Hannah M. Zinnert; Matthew F. Gladfelter; Suzanne E. Tenison; H. Peyton Poe; Kate L. Merrill; Ashley V. Hennessey; Michael B. McDonald; Dengjun Wang; H. Allen Torbert; Alan E. Wilson (Aquaculture, 2024)

Effect-based monitoring of two rivers under urban and agricultural influence reveals a range of biological activities in sediment and water extracts - Frederic D.L. Leusch; Hamish Allen; Nuwan A.L. De Silva; Roger Hodson; Matthew Johnson; Peta A. Neale; Michael Stewart; Louis A. Tremblay; Taylor Wilde; Grant L. Northcott (Journal of Environmental Management, 2024)

Division time (td) for in situ growth measurements demonstrates thermal ecotypes of Karlodinium veneficum - Erik L. J. E. Broemsen; Allen R. Place; Matthew W. Parrow (Harmful Algae, 2024)

A new climatology of South American extratropical cyclogenesis with an intercomparison among ERA5 , JRA55 and the Brazilian Navy - Luthiene Dalanhese; Jacob Stuivenvolt‐Allen; Matthew LaPlante; Shih‐Yu Wang; Thales Lessa Costa; Heloisa Dias Ferreira da Silva; Andre Luiz Belem (International Journal of Climatology, 2023)
In South America, the most destructive extratropical cyclones occur over the southeastern quadrant of the continent, a region that includes some of the world's largest population centres. However, there are few studies of cyclogenesis in this region, and little is known about how the varying origins of these storms impact subsequent behaviour. By supplementing an observational record with current reanalysis data, this study reveals the general characteristics of cyclones that develop in the lee regions of the Andes and those that develop nearer the Atlantic coast. The comparative climatologies demonstrate that cyclone development in these separate contexts is driven by topography, local atmospheric circulations and basin‐scale climate oscillations. The analysis further reveals a low‐frequency seesaw of lee and coastal cyclogenesis, with cross‐basin ocean temperature differences playing a teleconnectional role.

Positive and negative impacts of flue gas desulfurization (FGD) gypsum on water quality - Hannah M. Zinnert; Matthew F. Gladfelter; H. Peyton Poe; Kate L. Merrill; Ashley V. Hennessey; Michael B. McDonald; Dengjun Wang; H. Allen Torbert; Alan E. Wilson (Journal of Environmental Management, 2023)

Net-zero CO2 by 2050 scenarios for the United States in the Energy Modeling Forum 37 study - Morgan Browning; James McFarland; John Bistline; Gale Boyd; Matteo Muratori; Matthew Binsted; Chioke Harris; Trieu Mai; Geoff Blanford; Jae Edmonds; Allen A. Fawcett; Ozge Kaplan; et al. (Energy and Climate Change, 2023)

Hydrodynamic response to bathymetric changes in Tampa Bay, Florida - Jing Chen; Yonggang Liu; Robert H. Weisberg; Steven A. Murawski; Sherryl Gilbert; David F. Naar; Lianyuan Zheng; Matthew Hommeyer; Catherine Dietrick; Mark E. Luther; Cheryl Hapke; Edward Myers; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Using social network analysis to track the evolution of Pacific food system research collaborations over time - Rachel S. Friedman; Ellis Mackenzie; Asenati L. Chan-Tung; Matthew G. Allen; Steven Crimp (Regional Environmental Change, 2023)
Climate change undermines the foundations of food and nutrition security, making it crucial to understand and improve the current research collaborations striving to fill knowledge gaps about the impacts on food systems. This study focuses on the network of research actors working on food systems and climate change in Pacific Island Countries and Territories (PICTs), a region particularly vulnerable to climate change, and actively integrating knowledge about climate impacts to inform adaptation planning. Specifically, this study looks at co-publication as a form of research collaboration and co-production, using network analysis to understand who are the prominent organizational actors driving knowledge development in the region. Overall, we found a distinct core of these organizations engaged in the research space, dominated in number by academic institutions largely based in Australia, the USA, and New Zealand, but knit together through the interactions of the regional government agencies of the Pacific Islands. Over time, the network of research collaboration on climate change and food systems in the region has grown and diversified. While regional Pacific institutions have remained central actors throughout, national and subnational actors are still in the minority, raising questions about efforts to decolonize research in the region. Furthermore, greater interaction between peripheral actors and the core (especially Pacific actors) could help integrate new research into Pacific knowledge bases and decision-making. Ultimately, when facing the novel conditions that climate change brings, combining the infusion of new knowledge and innovation with local expertise and ownership is critical.

Shifted out: The well-being and justice implications of evening and night commuting - Matthew Palm; Jeff Allen; Steven Farber (Transportation Research Part D: Transport and Environment, 2023)

Global biome patterns of the Middle and Late Pleistocene - Brian Huntley; Judy R. M. Allen; Matthew Forrest; Thomas Hickler; Ralf Ohlemüller; Joy S. Singarayer; Paul J. Valdes (Journal of Biogeography, 2023)
Our primary aim was to assess the hypothesis that distinctive features of the patterns of vegetation change during successive Quaternary glacial–interglacial cycles reflect climatic differences arising from forcing differences. We addressed this hypothesis using 207 half‐degree resolution global biome pattern simulations, for time slices between 800 and 2 ka, made using the LPJ‐GUESS dynamic global vegetation model. Simulations were driven using ice‐core atmospheric CO 2 concentrations, Earth's obliquity, and outputs from a pre‐industrial and 206 palaeoclimate experiments; four additional simulations were driven using projected future CO 2 concentrations. Climate experiments were run using HadCM3. Using a rule‐based approach, above‐ground biomass and leaf area index of LPJ‐GUESS plant functional types were used to infer each grid cell's biome. The hypothesis is supported by the palaeobiome simulations. To enable comparisons with the climatic forcing, multivariate analyses were performed of global vegetation pattern dissimilarities between simulations. Results showed generally similar responses to glacial–interglacial climatic variations during each cycle, although no two interglacials or glacials had identical biome patterns. Atmospheric CO 2 concentration was the strongest driver of the dissimilarity patterns. Dissimilarities relative to the time slice with the lowest atmospheric CO 2 concentration show the log‐linear relationship to atmospheric CO 2 concentration expected of an index of ecocarbon sensitivity. For each simulation, extent and total above‐ground biomass of each biome were calculated globally and for three longitudinal segments corresponding to the major continental regions. Mean and minimum past extents of forest biomes, notably Temperate Summergreen Forest, in the three major continental regions strongly parallel relative tree diversities, hence supporting the hypothesis that past biome extents played an important role in determining present diversity. Albeit that they reflect the climatic consequences only of the faster Earth system components, simulated potential future biome patterns are unlike any during the past 800 ky, and likely will continue to change markedly for millennia if projected CO 2 concentrations are realised.

Topographic information improves simulated patterns of post‐fire conifer regeneration in the southwest United States - Chang Gyo Jung; Alisa R. Keyser; Cecile C. Remy; Daniel Krofcheck; Craig D. Allen; Matthew D. Hurteau (Global Change Biology, 2023)
The western United States is projected to experience more frequent and severe wildfires in the future due to drier and hotter climate conditions, exacerbating destructive wildfire impacts on forest ecosystems such as tree mortality and unsuccessful post‐fire regeneration. While empirical studies have revealed strong relationships between topographical information and plant regeneration, ecological processes in ecosystem models have either not fully addressed topography‐mediated effects on the probability of plant regeneration, or the probability is only controlled by climate‐related factors, for example, water and light stresses. In this study, we incorporated seedling survival data based on a planting experiment in the footprint of the 2011 Las Conchas Fire into the Photosynthesis and EvapoTranspiration (PnET) extension of the LANDIS‐II model by adding topographic and an additional climatic variable to the probability of regeneration. The modified algorithm included topographic parameters such as heat load index and ground slope and spring precipitation. We ran simulations on the Las Conchas Fire landscape for 2012–2099 using observed and projected climate data (i.e., Representative Concentration Pathway 4.5 and 8.5). Our modification significantly reduced the number of regeneration events of three common southwestern conifer tree species (piñon, ponderosa pine, and Douglas‐fir), leading to decreases in aboveground biomass, regardless of climate scenario. The modified algorithm decreased regeneration at higher elevations and increased regeneration at lower elevations relative to the original algorithm. Regenerations of three species also decreased in eastern aspects. Our findings suggest that ecosystem models may overestimate post‐fire regeneration events in the southwest United States. To better represent regeneration processes following wildfire, ecosystem models need refinement to better account for the range of factors that influence tree seedling establishment. This will improve model utility for projecting the combined effects of climate and wildfire on tree species distributions.

Effects of temperature and subspecies during critical early life history stages of largemouth bass (Micropterus salmoides) - Gavin L. Aguilar; Josh Sakmar; Allen Nicholls; Matthew K. Litvak; Hana N. Hess; Timothy J. Bruce; Helen R. Montague; Anita M. Kelly; Luke A. Roy; Moisés A. Bernal; Sebastian N. Politis; Ian A.E. Butts (Aquaculture, 2023)

Understanding the global warming potential of circular design strategies: Life cycle assessment of a design-for-disassembly building - Matthew Roberts; Stephen Allen; Joanna Clarke; Justin Searle; David Coley (Sustainable Production and Consumption, 2023)

Intertidal Creek Pool Nekton Assemblages: Long-term Patterns in Diversity and Abundance in a Warm-Temperate Estuary - Matthew E. Kimball; Bruce W. Pfirrmann; Dennis M. Allen; Virginia Ogburn-Matthews; Paul D. Kenny (Estuaries and Coasts, 2023)

Optimal risk-based allocation of disease surveillance effort for clustered disease outbreaks - Matthew J. Clement; Anne Justice-Allen; Jonathon D. Heale (Preventive Veterinary Medicine, 2023)

Design of a collector for sampling volcanic ash using unmanned aerial systems - James MacLeod; Kieran Wood; Thomas Rendall; Matthew Watson; Christian Allen; Madeleine Reader; Josh Lucas; Thomas Richardson (Journal of Aerosol Science, 2023)

Development and Evaluation of High-Density SNP Arrays for the Eastern Oyster Crassostrea virginica - Ximing Guo; Jonathan B. Puritz; Zhenwei Wang; Dina Proestou; Standish Allen; Jessica Small; Klara Verbyla; Honggang Zhao; Jaime Haggard; Noah Chriss; Dan Zeng; Kathryn Lundgren; et al. (Marine Biotechnology, 2023)

Amplified drought trends in Nepal increase the potential for Himalayan wildfires - Binod Pokharel; Shankar Sharma; Jacob Stuivenvolt-Allen; Shih-Yu Simon Wang; Matthew LaPlante; Robert R. Gillies; Sujan Khanal; Michael Wehner; Alan Rhoades; Kalpana Hamal; Benjamin Hatchett; Wan-Yu Liu; et al. (Climatic Change, 2023)

Toward Identifying the Critical Ecological Habitat of Larval Fishes: An Environmental DNA Window into Fisheries Management - Erin Satterthwaite; Andrew Allen; Robert Lampe; Zachary Gold; Andrew Thompson; Noelle Bowlin; Rasmus Swalethorp; Kelly Goodwin; Elliott Hazen; Steven Bograd; Stephanie Matthews; Brice Semmens (Oceanography, 2023)
Environmental DNA (eDNA)-based ecological co-occurrence networks can provide a valuable tool for fisheries and conservation management. In the past, it was nearly impossible to explore the microscopic world of larval fishes in one sampling event. Now, eDNA data and ecological co-occurrence network modeling provide windows into ecosystems that support larval fishes and upon which subsequent fisheries rely. Thus, there is great potential for eDNA methods coupled with ecological network analyses to provide a holistic understanding of community composition and species interactions and to develop indicators for fisheries and ecosystem-based management.

Lack of a Zn/Co substitution ability in the polar diatom Chaetoceros neogracile RS19 - Riss M. Kellogg; Dawn M. Moran; Matthew R. McIlvin; Adam V. Subhas; Andrew E. Allen; Mak A. Saito (Limnology and Oceanography, 2022)
Functional substitution of the essential trace metals zinc (Zn) and cobalt (Co) within metalloenzymes has been well documented in marine diatoms and is known to be prevalent among varying genera and species. In contrast to the majority of species studied to date, we find that the polar diatom Chaetoceros neogracile RS19, originally isolated from the Ross Sea, Antarctica, has a Zn requirement that cannot be met by Co and thus does not demonstrate a Zn/Co substitution ability as assessed by growth rate. We investigated this diatom's inability to use Co to alleviate Zn‐limited growth rates at the transporter, sensor/chaperone, and metalloenzyme level using metal quota and proteomic analyses of cultures grown over a range of Zn and Co availability. Analysis of total cellular metal quotas revealed that, although incapable of substitution, this diatom still actively assimilated dissolved Co. We furthermore observed distinct trends in the abundance levels of putative α and θ‐CAs, ZIP transporters, Zn fingers, and a Zn chaperone in response to increasing media Zn 2+ . Overall, Co appears to be transported into the cell, but not efficiently utilized by Zn metalloenzymes.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Post release monitoring of rehabilitated gray seal pups over large temporal and spatial scales - Sue Sayer; Rebecca Allen; Katie Bellman; Marion Beaulieu; Tamara Cooper; Natalie Dyer; Kirsten Hockin; Kate Hockley; Dan Jarvis; Grace Jones; Paul Oaten; Natalie Waddington; et al. (Marine Mammal Science, 2022)
Wildlife rescue and rehabilitation is used globally to aid the conservation and welfare of marine species, however, postrelease monitoring is challenging. Here, long‐term, regional postrelease monitoring provides feedback for rehabilitation centers for gray seals ( Halichoerus grypus ). Data from 1,094 rehabilitated gray seals over 19 years across the southwest UK were examined to assess postrelease survivorship and the impact of release site on movements and range. Using flipper tags combined with photo identification, 391 rehabilitated seals (35.7%) were resighted, including 188 seals (17.2%) that were traced back to a specific rehabilitated individual with release data. The maximum monitoring duration for a single rehabilitated seal was 17 years, although the majority (151/188; 80%) were sighted for less than 5 years and 80/188 (43%) were resighted for less than a year. Almost all 188 traced rehabilitated seals ( n = 176, 93.6%) visited the St Ives Bay Wild Site, yet only half had been released at the adjacent St Ives Bay Release Site. Rehabilitated seals had similar dispersal patterns to their wild conspecifics but over a smaller area. Once released, rehabilitated animals face the same threats as their wild counterparts.

A National Status Report on United States Coral Reefs Based on 2012–2018 Data From National Oceanic and Atmospheric Administration’s National Coral Reef Monitoring Program - Erica K. Towle; E. Caroline Donovan; Heath Kelsey; Mary E. Allen; Hannah Barkley; Jeremiah Blondeau; Russell E. Brainard; Annie Carew; Courtney S. Couch; Maria K. Dillard; C. Mark Eakin; Kimberly Edwards; et al. (Frontiers in Marine Science, 2022)
National Oceanic and Atmospheric Administration’s Coral Reef Conservation Program supports the National Coral Reef Monitoring Program (NCRMP) in the United States Pacific, Atlantic, Caribbean, and Gulf of Mexico. NCRMP conducts standardized observations of biological, climatic, and socioeconomic indicators across American Samoa, Guam, the Main Hawaiian Islands, the Northwestern Hawaiian Islands, the Northern Mariana Islands, the Pacific Remote Islands, Florida, the Flower Garden Banks, Puerto Rico, and the United States Virgin Islands. NCRMP provides periodic, national-level assessments of the status of United States coral reef ecosystems and communities connected to them. In 2014, NCRMP partnered with the University of Maryland Center for Environmental Science on an unprecedented collaboration between federal and jurisdictional/state agencies, academia, and non-governmental organizations to synthesize NCRMP data into a reporting format designed to be accessible and relevant to the public and policy makers. The process involved multi-year data analyses of key benthic, fish, and climate indicators. In populated jurisdictions, socioeconomic data were integrated to assess public support for management actions, participation in pro-environmental behaviors, and awareness of threats to coral reefs. Jurisdictions were scored using a report-card scale (0–100%) by establishing references for each indicator using best-available historical data or expert opinion where historical data did not exist or were not statistically comparable. Despite overall ecosystem scores of Fair for all combined Atlantic (70%) and Pacific (74%) jurisdictions, the current trend is downward with a majority of United States coral reefs declining and vulnerable to further degradation. Remote, uninhabited reefs had an advantage with respect to reef fish population scores, i.e., Flower Garden Banks (85%) and Pacific Remote Islands (93%), when compared to populated location scores, i.e., Puerto Rico (63%) and Main Hawaiian Islands (66%). All coral reefs are highly impacted by climate change, and climate impacts were more pronounced than expected on remote reefs, i.e., the Northwestern Hawaiian Islands (58%). Presenting results in a report-card style facilitates communication to the public and policy makers, and provides a useful mechanism to garner support for management actions such as expanding protected areas; enforcing existing regulations; increasing climate change education; reducing land-based sources of pollution; and other actions to improve the trajectory of coral reef ecosystem conditions.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Asymmetry across international borders: Research, fishery and management trends and economic value of the giant sea bass ( Stereolepis gigas ) - Arturo Ramírez‐Valdez; Timothy J. Rowell; Katherine E. Dale; Matthew T. Craig; Larry G. Allen; Juan Carlos Villaseñor‐Derbez; Andrés M. Cisneros‐Montemayor; Arturo Hernández‐Velasco; Jorge Torre; Jennifer Hofmeister; Brad E. Erisman (Fish and Fisheries, 2021)
Co‐operation in the management of shared fish stocks is often necessary to achieve sustainability and reduce uncertainty. The United States of America (USA) and Mexico share a number of fish stocks and marine ecosystems, while there is some binational co‐operation in scientific research, unilateral management decisions are generally the rule. We present a case study using the giant sea bass ( Stereolepis gigas , Polyprionidae) to highlight how these management and research asymmetries can skew national perceptions of population status for a fully transboundary species. Scientific publications and annual funding related to giant sea bass are 7x and 25x higher in the USA, respectively, despite the fact that 73% of the species’ range occurs in Mexico. Conversely, annual fishery production and consumptive value of giant sea bass in Mexico are 19x and 3.5x higher than in the USA, respectively, while the non‐consumptive value related to dive ecotourism is 76x higher in the USA. These asymmetries have generated a distorted view of the population status of the giant sea bass across its entire range. This and other factors related to historical fishery dynamics and policy must be accounted for when assessing population status, and subsequent appropriate management responses, across geopolitical boundaries.

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

Projected climatic changes lead to biome changes in areas of previously constant biome - Brian Huntley; Judy R. M. Allen; Matthew Forrest; Thomas Hickler; Ralf Ohlemüller; Joy S. Singarayer; Paul J. Valdes (Journal of Biogeography, 2021)
Aim Recent studies in southern Africa identified past biome stability as an important predictor of biodiversity. We aimed to assess the extent to which past biome stability predicts present global biodiversity patterns, and the extent to which projected climatic changes may lead to eventual biome changes in areas with constant past biome. Location Global. Taxon Spermatophyta; terrestrial vertebrates. Methods Biome constancy was assessed and mapped using results from 89 dynamic global vegetation model simulations, driven by outputs of palaeoclimate experiments spanning the past 140 ka. We tested the hypothesis that terrestrial vertebrate diversity is predicted by biome constancy. We also simulated potential future vegetation, and hence potential future biome patterns, and quantified and mapped the extent of projected eventual future biome change in areas of past constant biome. Results Approximately 11% of global ice‐free land had a constant biome since 140 ka. Apart from areas of constant Desert, many areas with constant biome support high species diversity. All terrestrial vertebrate groups show a strong positive relationship between biome constancy and vertebrate diversity in areas of greater diversity, but no relationship in less diverse areas. Climatic change projected by 2100 commits 46%–66% of global ice‐free land, and 34%–52% of areas of past constant biome (excluding areas of constant Desert) to eventual biome change. Main conclusions Past biome stability strongly predicts vertebrate diversity in areas of higher diversity. Future climatic changes will lead to biome changes in many areas of past constant biome, with profound implications for biodiversity conservation. Some projected biome changes will result in substantial reductions in biospheric carbon sequestration and other ecosystem services.

Watershed and streambank erosion modeling in a coldwater stream using the GWLF-E model: application and evaluation - Daniel T. L. Myers; Richard R. Rediske; James N. McNair; Matthew E. Allen (Modeling Earth Systems and Environment, 2021)

Expert opinion on American common eiders in eastern North America: international information needs for future conservation - Kristen Noel; Nic McLellan; Scott Gilliland; Karel A. Allard; Brad Allen; Shawn Craik; Anaïs Demagny; Matthew D. English; Antony Diamond; Jean-François Giroux; Alan Hanson; H. W. Heusmann; et al. (Socio-Ecological Practice Research, 2021)

Neuropsychological Assessment and Screening in Heart Failure: a Meta-Analysis and Systematic Review - Eric J. Connors; Alexander O. Hauson; Brianna D. Barlet; Sharis Sarkissians; Nicholas P. Stelmach; Alyssa D. Walker; Natasha M. Nemanim; Kristina L. Greenwood; Nicholas J. Chesher; Scott C. Wollman; Kenneth E. Allen; Matthew G. Hall; et al. (Neuropsychology Review, 2021)

Neighboring colonies influence uptake of thermotolerant endosymbionts in threatened Caribbean coral recruits - Olivia M. Williamson; Corinne E. Allen; Dana E. Williams; Matthew W. Johnson; Margaret W. Miller; Andrew C. Baker (Coral Reefs, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Simulated Increases in Fire Activity Reinforce Shrub Conversion in a Southwestern US Forest - Alisa R. Keyser; Dan J. Krofcheck; Cécile C. Remy; Craig D. Allen; Matthew D. Hurteau (Ecosystems, 2020)

Homogeneous environmental selection dominates microbial community assembly in the oligotrophic South Pacific Gyre - Ro Allen; Linn J. Hoffmann; Matthew J. Larcombe; Ziva Louisson; Tina C. Summerfield (Molecular Ecology, 2020)
Oligotrophic subtropical gyres are the largest continuous biomes on Earth and play a key role in global biogeochemical cycles. Microbial communities govern primary production and carbon cycling in the oligotrophic South Pacific Gyre, yet the ecological processes which underpin microbial biogeography in the region remain understudied. We investigated microbial biogeography and community assembly processes at three depths over a ~2,000‐km the transect was longitudinal, so ran from 32°S, 170°W to 32°S, 152°W). Thus the latitude (32°S) was constant. Microbial communities in the surface waters (15 and 50 m) were remarkably similar across the transect, whilst communities at the deep chlorophyll maximum were distinct from the surface waters and displayed greater compositional heterogeneity. An ecological null model approach indicated that homogeneous selection was the dominant community assembly process in both the surface waters (100%) and at the deep chlorophyll maximum (91.81%), although variable selection (2.34%) and stochastic processes (5.85%) had a minor influence at the deep chlorophyll maximum. Homogeneous selection (76.69%77.90%), dispersal limitation (15.00%–20.05%) and variable selection (3.01%–7.11%) influenced community assembly between the surface waters and the deep chlorophyll maximum. Seawater density and temperature, which were correlated, were the most important environmental modulators of the balance between stochastic and deterministic assembly processes. Our findings demonstrate remarkable similarity in microbial community composition across longitudinal scales in the oligotrophic South Pacific Gyre, underpinned by strong environmental selection which overwhelms the influence of ecological drift. These data significantly advance our understanding of microbial community dynamics in the oligotrophic subtropical gyres which dominate the Earth's surface.

Global vegetation patterns of the past 140,000 years - Judy R. M. Allen; Matthew Forrest; Thomas Hickler; Joy S. Singarayer; Paul J. Valdes; Brian Huntley (Journal of Biogeography, 2020)
Aim Insight into global biome responses to climatic and other environmental changes is essential to address key questions about past and future impacts of such changes. By simulating global biome patterns 140 ka to present, we aimed to address important questions about biome changes during this interval. Location Global. Taxon Spermatophyta. Methods Using the LPJ‐GUESS dynamic global vegetation model, we made 89 simulations driven using ice‐core atmospheric CO 2 concentrations, Earth's obliquity, and outputs from a pre‐industrial and 88 palaeoclimate experiments run using HadCM3. Experiments were run for 81 time slices between 1 and 140 ka, seven ‘hosing’ experiments also being run, using a 1‐Sv freshwater flux to the North Atlantic, for time slices corresponding to Heinrich Events H0–H6. Using a rule‐based approach, based on carbon mass and leaf area index of the LPJ‐GUESS plant functional types, the biome was inferred for each grid cell. Biomes were mapped, and the extent and total vegetation biomass of each biome, and total global vegetation biomass, estimated. Results Substantial changes in biome extents and locations were found on all vegetated continents. Although the largest magnitude changes were in Eurasia, important changes were seen in tropical latitudes and the Southern Hemisphere. Total global extent of most biomes varied on multi‐millennial (orbital) time scales, although some (e.g. Tropical Raingreen Forest) responded principally to the c. 100‐kyr glacial–interglacial cycle and others (e.g. Temperate Broad‐leaved Evergreen Forest) mainly to the c. 20‐kyr precession cycle. Many also responded to millennial contrasts between stadial (‘hosing’) and interstadial climates, with some (e.g. Tropical Evergreen Forest) showing stronger responses than to the multi‐millennial changes. Main conclusions No two time slices had identical biome patterns. Even equivalent Holocene and last interglacial time slices, and the last and penultimate glacial maxima, showed important differences. Only a small proportion of global land area experienced no biome change since 140 ka; many places experienced multiple biome changes. These modelling experiments provided little evidence for long‐term biome stability.

Cancer mortality risk, fine particulate air pollution, and smoking in a large, representative cohort of US adults - Nathan C. Coleman; Richard T. Burnett; Joshua D. Higbee; Jacob S. Lefler; Ray M. Merrill; Majid Ezzati; Julian D. Marshall; Sun-Young Kim; Matthew Bechle; Allen L. Robinson; C. Arden Pope (Cancer Causes & Control, 2020)

Decadal-Scale Changes in Subtidal Nekton Assemblages in a Warm-Temperate Estuary - Matthew E. Kimball; Dennis M. Allen; Paul D. Kenny; Virginia Ogburn-Matthews (Estuaries and Coasts, 2020)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Tidal Stage Mediates Periodic Asynchrony Between Predator and Prey Nekton in Salt Marsh Creeks - Kevin M. Boswell; Matthew E. Kimball; Guillaume Rieucau; Julien G. A. Martin; Dale A. Jacques; Daniel Correa; Dennis M. Allen (Estuaries and Coasts, 2019)

Site Fidelity and Habitat Use by Young-of-the-Year Transient Fishes in Salt Marsh Intertidal Creeks - Jason A. Garwood; Dennis M. Allen; Matthew E. Kimball; Kevin M. Boswell (Estuaries and Coasts, 2019)

Global patterns of body size evolution in squamate reptiles are not driven by climate - Alex Slavenko; Anat Feldman; Allen Allison; Aaron M. Bauer; Monika Böhm; Laurent Chirio; Guarino R. Colli; Indraneil Das; Tiffany M. Doan; Matthew LeBreton; Marcio Martins; Danny Meirte; et al. (Global Ecology and Biogeography, 2019)
Aim Variation in body size across animal species underlies most ecological and evolutionary processes shaping local‐ and large‐scale patterns of biodiversity. For well over a century, climatic factors have been regarded as primary sources of natural selection on animal body size, and hypotheses such as Bergmann's rule (the increase of body size with decreasing temperature) have dominated discussions. However, evidence for consistent climatic effects, especially among ectotherms, remains equivocal. Here, we test a range of key hypotheses on climate‐driven size evolution in squamate reptiles across several spatial and phylogenetic scales. Location Global. Time period Extant. Major taxa studied Squamates (lizards and snakes). Methods We quantified the role of temperature, precipitation, seasonality and net primary productivity as drivers of body mass across ca. 95% of extant squamate species (9,733 spp.). We ran spatial autoregressive models of phylogenetically corrected median mass per equal‐area grid cell. We ran models globally, across separate continents and for major squamate clades independently. We also performed species‐level analyses using phylogenetic generalized least square models and linear regressions of independent contrasts of sister species. Results Our analyses failed to identify consistent spatial patterns in body size as a function of our climatic predictors. Nearly all continent‐ and family‐level models differed from one another, and species‐level models had low explanatory power. Main conclusions The global distribution of body mass among living squamates varies independently from the variation in multiple components of climate. Our study, the largest in spatial and taxonomic scale conducted to date, reveals that there is little support for a universal, consistent mechanism of climate‐driven size evolution within squamates.

Correction to: The Neural Substrate of Reward Anticipation in Health: A Meta-Analysis of fMRI Findings in the Monetary Incentive Delay Task - Robin Paul Wilson; Marco Colizzi; Matthijs Geert Bossong; Paul Allen; Matthew Kempton; Sagnik Bhattacharyya (Neuropsychology Review, 2018)

The Neural Substrate of Reward Anticipation in Health: A Meta-Analysis of fMRI Findings in the Monetary Incentive Delay Task - Robin Paul Wilson; Marco Colizzi; Matthijs Geert Bossong; Paul Allen; Matthew Kempton; Sagnik Bhattacharyya (Neuropsychology Review, 2018)

Associations of dietary fat with risk of early neoplasia in the proximal colon in a population-based case–control study - Allen Mo; Rong Wu; James P. Grady; Matthew P. Hanley; Margaret Toro; Helen Swede; Thomas J. Devers; Terryl J. Hartman; Daniel W. Rosenberg (Cancer Causes & Control, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

Nekton Use of Flooded Salt Marsh and an Assessment of Intertidal Creek Pools as Low-Tide Refuges - Dennis M. Allen; Virginia Ogburn-Matthews; Paul D. Kenny (Estuaries and Coasts, 2017)

The longevity of para-aminopropiophenone (PAPP) wild dog baits and the implications for effective and safe baiting campaigns - Matthew Gentle; James Speed; Benjamin L. Allen; Stacy Harris; Hellen Haapakoski; Kerry Bell (Environmental Science and Pollution Research, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Estimating Carbon Budgets for Ambitious Climate Targets - H. Damon Matthews; Jean-Sébastien Landry; Antti-Ilari Partanen; Myles Allen; Michael Eby; Piers M. Forster; Pierre Friedlingstein; Kirsten Zickfeld (Current Climate Change Reports, 2017)

Long-Term Functional Efficacy of a Novel Electrospun Poly(Glycerol Sebacate)-Based Arterial Graft in Mice - Ramak Khosravi; Cameron A. Best; Robert A. Allen; Chelsea E. T. Stowell; Ekene Onwuka; Jennifer J. Zhuang; Yong-Ung Lee; Tai Yi; Matthew R. Bersi; Toshiharu Shinoka; Jay D. Humphrey; Yadong Wang; et al. (Annals of Biomedical Engineering, 2016)

Improving niche and range estimates with Maxent and point process models by integrating spatially explicit information - Cory Merow; Jenica M. Allen; Matthew Aiello‐Lammens; John A. Silander (Global Ecology and Biogeography, 2016)
Aim Accurate spatial information on species occurrence is essential to address global change. Models for presence‐only data are central to predicting species distributions because these represent the only geographical information available for many species. In this paper we introduce extensions to incorporate a variety of types of additional spatially explicit sources of information in Maxent and Poisson point process models. This spatial information comes from the output of other statistical or conceptual models. Innovation Our approach relies on minimizing the relative (or cross) entropy (known as Minxent) between the predicted distribution and a prior distribution. In many scenarios, researchers have some additional information or expectations about the species distribution, such as outputs from previous models. Here, we show how to use this information to improve predictions of both niche models and spatial distributions, depending on what types of spatially explicit prior information is available and how it is incorporated in the model. Main conclusions We illustrate applications of Minxent that include models for sampling bias, explicitly incorporating dispersal/other ecological processes, combining native and invasive range data, incorporating expert maps, and borrowing strength across taxonomic relatives. These applications focus on addressing biological scenarios where range modelling is extremely challenging – non‐equilibrium species distributions and rare and narrowly distributed species – due to data limitations. When data are limited, we are typically forced to make informal assumptions or lean on predictions of other models in order to obtain useful predictions; our applications of Minxent provide a formal way of describing these assumptions and connections to other models.

The impacts of increasing drought on forest dynamics, structure, and biodiversity in the United States - James S. Clark; Louis Iverson; Christopher W. Woodall; Craig D. Allen; David M. Bell; Don C. Bragg; Anthony W. D'Amato; Frank W. Davis; Michelle H. Hersh; Ines Ibanez; Stephen T. Jackson; Stephen Matthews; et al. (Global Change Biology, 2016)
We synthesize insights from current understanding of drought impacts at stand‐to‐biogeographic scales, including management options, and we identify challenges to be addressed with new research. Large stand‐level shifts underway in western forests already are showing the importance of interactions involving drought, insects, and fire. Diebacks, changes in composition and structure, and shifting range limits are widely observed. In the eastern US , the effects of increasing drought are becoming better understood at the level of individual trees, but this knowledge cannot yet be confidently translated to predictions of changing structure and diversity of forest stands. While eastern forests have not experienced the types of changes seen in western forests in recent decades, they too are vulnerable to drought and could experience significant changes with increased severity, frequency, or duration in drought. Throughout the continental United States, the combination of projected large climate‐induced shifts in suitable habitat from modeling studies and limited potential for the rapid migration of tree populations suggests that changing tree and forest biogeography could substantially lag habitat shifts already underway. Forest management practices can partially ameliorate drought impacts through reductions in stand density, selection of drought‐tolerant species and genotypes, artificial regeneration, and the development of multistructured stands. However, silvicultural treatments also could exacerbate drought impacts unless implemented with careful attention to site and stand characteristics. Gaps in our understanding should motivate new research on the effects of interactions involving climate and other species at the stand scale and how interactions and multiple responses are represented in models. This assessment indicates that, without a stronger empirical basis for drought impacts at the stand scale, more complex models may provide limited guidance.

Regurgitation Hemodynamics Alone Cause Mitral Valve Remodeling Characteristic of Clinical Disease States In Vitro - Patrick S. Connell; Anam F. Azimuddin; Seulgi E. Kim; Fernando Ramirez; Matthew S. Jackson; Stephen H. Little; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2016)

Developing a genetic baseline for the yellowtail amberjack species complex, Seriola lalandi sensu lato, to assess and preserve variation in wild populations of these globally important aquaculture species - Catherine M. Purcell; Chris L. Chabot; Matthew T. Craig; Natalie Martinez-Takeshita; Larry G. Allen; John R. Hyde (Conservation Genetics, 2015)

Framing food security in the Pacific Islands: empirical evidence from an island in the Western Pacific - Matthew G. Allen (Regional Environmental Change, 2015)

Tidal and diel variations in abundance and schooling behavior of estuarine fish within an intertidal salt marsh pool - Guillaume Rieucau; Kevin M. Boswell; Matthew E. Kimball; Gabriel Diaz; Dennis M. Allen (Hydrobiologia, 2015)

Mapping the distribution of maize streak virus genotypes across the forest and transition zones of Ghana - Allen Oppong; Samuel K. Offei; Kwadwo Ofori; Hans Adu-Dapaah; Joseph N. L. Lamptey; Brigitta Kurenbach; Matthew Walters; Dionne N. Shepherd; Darren P. Martin; Arvind Varsani (Archives of Virology, 2015)

Dietary nano-chromium tripicolinate increases feed intake and decreases plasma cortisol in finisher gilts during summer - Alex Tsungyu Hung; Brian Joseph Leury; Matthew Allen Sabin; Cherie Louise Collins; Frank Rowland Dunshea (Tropical Animal Health and Production, 2014)

Host genetics and viral load in primary HIV-1 infection: clear evidence for gene by sex interactions - Xuelin Li; Matthew A. Price; Dongning He; Anatoli Kamali; Etienne Karita; Shabir Lakhi; Eduard J. Sanders; Omu Anzala; Pauli N. Amornkul; Susan Allen; Eric Hunter; Richard A. Kaslow; et al. (Human Genetics, 2014)

Contrast agents for MRI: 30+ years and where are we going? - Valérie C. Pierre; Matthew J. Allen; Peter Caravan (JBIC Journal of Biological Inorganic Chemistry, 2014)

Methionine synthase interreplacement in diatom cultures and communities: Implications for the persistence of B 12 use by eukaryotic phytoplankton - Erin M. Bertrand; Dawn M. Moran; Matthew R. McIlvin; Jeffrey M. Hoffman; Andrew E. Allen; Mak A. Saito (Limnology and Oceanography, 2013)
Three proteins related to vitamin B 12 metabolism in diatoms were quantified via selected reaction monitoring mass spectrometry: B 12 ‐dependent and B 12 ‐independent methionine synthase (MetH, MetE) and a B 12 acquisition protein (CBA1). B 12 ‐mediated interreplacement of MetE and MetH metalloenzymes was observed in Phaeodactylum tricornutum where MetH abundance was highest (0.06 fmol µg −1 protein) under high B 12 and MetE abundance increased to 3.25 fmol µg −1 protein under low B 12 availability. Maximal MetE abundance was 60‐fold greater than MetH, consistent with the expected ∼ 50–100‐fold larger turnover number for MetH. MetE expression resulted in 30‐fold increase in nitrogen and 40‐fold increase in zinc allocated to methionine synthase activity under low B 12 . CBA1 abundance was 6‐fold higher under low‐B 12 conditions and increased upon B 12 resupply to starved cultures. While biochemical pathways that supplant B 12 requirements exist and are utilized by organisms such as land plants, B 12 use persists in eukaryotic phytoplankton. This study suggests that retention of B 12 utilization by phytoplankton results in resource conservation under conditions of high B 12 availability. MetE and MetH abundances were also measured in diatom communities from McMurdo Sound, verifying that both these proteins are expressed in natural communities. These protein measurements are consistent with previous studies suggesting that B 12 availability influences Antarctic primary productivity. This study illuminates controls on expression of B 12 ‐related proteins, quantitatively assesses the metabolic consequences of B 12 deprivation, and demonstrates that mass spectrometry‐based protein measurements yield insight into the functioning of marine microbial communities.

Windstorm damage and forest recovery: accelerated succession, stand structure, and spatial pattern over 25 years in two Minnesota forests - Matthew S. Allen; Vaskar Thapa; José Ramón Arévalo; Michael W. Palmer (Plant Ecology, 2012)

Hyperaccumulation of nickel by Alyssum corsicum is related to solubility of Ni mineral species - Tiziana Centofanti; Matthew G. Siebecker; Rufus L. Chaney; Allen P. Davis; Donald L. Sparks (Plant and Soil, 2012)

In situ rates of body growth and palp regeneration of a spionid polychaete following simulated sublethal predation - John Allen Matthews; Brian T. Hentschel (Marine Biology, 2012)

Biological control of Melaleuca quinquenervia: an Everglades invader - Ted D. Center; Matthew F. Purcell; Paul D. Pratt; Min B. Rayamajhi; Philip W. Tipping; Susan A. Wright; F. Allen Dray (BioControl, 2012)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Near real-time Feed On Offer (FOO) from MODIS for early season grazing management of Mediterranean annual pastures - Richard C. G. Smith; Matthew Adams; Stewart Gittins; Steve Gherardi; Duncan Wood; Stefan Maier; Richard Stovold; Graham Donald; Sarfraz Khohkar; Adrian Allen (International Journal of Remote Sensing, 2011)

Plasma matrix metalloproteinase-9 response to eccentric exercise of the elbow flexors - Molly C. Madden; William C. Byrnes; Jacob A. Lebin; Matthew E. Batliner; David L. Allen (European Journal of Applied Physiology, 2011)

Biomembrane force probe investigation of RNA dissociation - Christopher Brampton; Omar Wahab; Matthew R. Batchelor; Stephanie Allen; Philip M. Williams (European Biophysics Journal, 2011)

Calcium storage in plants and the implications for calcium biofortification - Maclin Dayod; Stephen Donald Tyerman; Roger Allen Leigh; Matthew Gilliham (Protoplasma, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Biological consequences of invasion by reed canary grass (Phalaris arundinacea) - Greg Spyreas; Brian W. Wilm; Allen E. Plocher; David M. Ketzner; Jeffrey W. Matthews; James L. Ellis; Edward J. Heske (Biological Invasions, 2010)

Sedimentation of acantharian cysts in the Iceland Basin: Strontium as a ballast for deep ocean particle flux, and implications for acantharian reproductive strategies - Patrick Martin; John T. Allen; Matthew J. Cooper; David G. Johns; Richard S. Lampitt; Richard Sanders; Damon A. H. Teagle (Limnology and Oceanography, 2010)
Acantharian cysts were discovered in sediment trap samples from spring 2007 at 2000 m in the Iceland Basin. Although these single‐celled organisms contribute to particulate organic matter flux in the upper mesopelagic, their contribution to bathypelagic particle flux has previously been found negligible. Four time‐series sediment traps were deployed and all collected acantharian cysts, which are reproductive structures. Across all traps, cysts contributed on average 3–22%, and 4–24% of particulate organic carbon and nitrogen (POC and PON) flux, respectively, during three separate collection intervals (the maximum contribution in any one trap was 48% for POC and 59% for PON). Strontium (Sr) flux during these 6 weeks reached 3 mg m −2 d −1 . The acantharian celestite (SrSO 4 ) skeleton clearly does not always dissolve in the mesopelagic as often thought, and their cysts can contribute significantly to particle flux at bathypelagic depths during specific flux events. Their large size (~ 1 mm) and mineral ballast result in a sinking rate of ~ 500 m d −1 ; hence, they reach the bathypelagic before dissolving. Our findings are consistent with a vertical profile of salinity‐normalized Sr concentration in the Iceland Basin, which shows a maximum at 1700 m. Profiles of salinity‐normalized Sr concentration in the subarctic Pacific reach maxima at ≤ 1500 m, suggesting that Acantharia might contribute to the bathypelagic particle flux there as well. We hypothesize that Acantharia at high latitudes use rapid, deep sedimentation of reproductive cysts during phytoplankton blooms so that juveniles can exploit the large quantity of organic matter that sinks rapidly to the deep sea following a bloom.

Enzymatic properties of the ferredoxin-dependent nitrite reductase from Chlamydomonas reinhardtii. Evidence for hydroxylamine as a late intermediate in ammonia production - Masakazu Hirasawa; Jatindra N. Tripathy; Frederik Sommer; Ramasamy Somasundaram; Jung-Sung Chung; Matthew Nestander; Mahima Kruthiventi; Masoud Zabet-Moghaddam; Michael K. Johnson; Sabeeha S. Merchant; James P. Allen; David B. Knaff (Photosynthesis Research, 2010)

Yield and nutritional responses to waterlogging of soybean cultivars - Matthew Douglas Rhine; Gene Stevens; Grover Shannon; Allen Wrather; David Sleper (Irrigation Science, 2010)

A Biogeochemical View of Estuarine Eutrophication: Seasonal and Spatial Trends and Correlations in the Delaware Estuary - Jonathan H. Sharp; Kohei Yoshiyama; Alexander E. Parker; Matthew C. Schwartz; Susan E. Curless; Allison Y. Beauregard; Justin E. Ossolinski; Allen R. Davis (Estuaries and Coasts, 2009)

Effects of an invasive plant on a desert sand dune landscape - Cameron W. Barrows; Edith B. Allen; Matthew L. Brooks; Michael F. Allen (Biological Invasions, 2009)

Threatened fishes of the world: Allotoca goslinei Smith and Miller, 1987 (Goodeidae) - Matthew R. Helmus; Lauren B. Allen; Omar Dominguez-Dominguez; Edmundo Díaz Pardo; Pablo Gesundheit; John Lyons; Norman Mercado Silva (Environmental Biology of Fishes, 2009)

Effects of cryptic mortality and the hidden costs of using length limits in fishery management - Lewis G Coggins; Matthew J Catalano; Micheal S Allen; William E Pine; Carl J Walters (Fish and Fisheries, 2007)
Fishery collapses cause substantial economic and ecological harm, but common management actions often fail to prevent overfishing. Minimum length limits are perhaps the most common fishing regulation used in both commercial and recreational fisheries, but their conservation benefits can be influenced by discard mortality of fish caught and released below the legal length. We constructed a computer model to evaluate how discard mortality could influence the conservation utility of minimum length regulations. We evaluated policy performance across two disparate fish life‐history types: short‐lived high‐productivity (SLHP) and long‐lived low‐productivity (LLLP) species. For the life‐history types, fishing mortality rates and minimum length limits that we examined, length limits alone generally failed to achieve sustainability when discard mortality rate exceeded about 0.2 for SLHP species and 0.05 for LLLP species. At these levels of discard mortality, reductions in overall fishing mortality (e.g. lower fishing effort) were required to prevent recruitment overfishing if fishing mortality was high. Similarly, relatively low discard mortality rates (>0.05) rendered maximum yield unobtainable and caused a substantial shift in the shape of the yield response surfaces. An analysis of fishery efficiency showed that length limits caused the simulated fisheries to be much less efficient, potentially exposing the target species and ecosystem to increased negative effects of the fishing process. Our findings suggest that for overexploited fisheries with moderate‐to‐high discard mortality rates, reductions in fishing mortality will be required to meet management goals. Resource managers should carefully consider impacts of cryptic mortality sources (e.g. discard mortality) on fishery sustainability, especially in recreational fisheries where release rates are high and effort is increasing in many areas of the world.

A genetic test for recruitment enhancement in Chesapeake Bay oysters, Crassostrea virginica, after population supplementation with a disease tolerant strain - Matthew P. Hare; Standish K. Allen; Paulette Bloomer; Mark D. Camara; Ryan B. Carnegie; Jenna Murfree; Mark Luckenbach; Donald Meritt; Cheryl Morrison; Kennedy Paynter; Kimberly S. Reece; Colin G. Rose (Conservation Genetics, 2006)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Genes controlling seed dormancy and pre-harvest sprouting in a rice-wheat-barley comparison - Chengdao Li; Peixiang Ni; Michael Francki; Adam Hunter; Yong Zhang; David Schibeci; Heng Li; Allen Tarr; Jun Wang; Mehmet Cakir; Jun Yu; Matthew Bellgard; et al. (Functional & Integrative Genomics, 2004)

Synthesis and visualization of a membrane-permeable MRI contrast agent - Matthew J. Allen; Thomas J. Meade (JBIC Journal of Biological Inorganic Chemistry, 2003)

The Creation of an Historical Meteorological Database for Environmental Dose Assessment - Allen H. Weber; Robert L. Buckley; Matthew J. Parker; Richard P. Harvey; David M. Hamby (Environmental Monitoring and Assessment, 2003)

Axial rod growth and age estimation of the sea pen, Halipteris willemoesi Kölliker - Matthew T. Wilson; Allen H. Andrews; Annette L. Brown; Erik E. Cordes (Hydrobiologia, 2002)